Acute gonococcal urethritis - H. Shatikkulamin; Chandana Shajil (IDCases)
Gonococcal urethritis is a sexually transmitted infection caused by obligate gram-negative diplococci, Neisseria gonorrhoeae. In a patient complaining of dysuria and urethral discharge, the diagnosis is typically confirmed by identifying the bacteria in mucosal secretions. Inadequately treated or untreated cases are at a risk of developing epididymo-orchitis, prostatitis and serious complications like disseminated gonococcal infection, meningitis, and endocarditis.